DAMPAK BRAND IMAGE SERTIFIKASI HALAL PRODUK SAMYANG TERHADAP SIKAP KONSUMEN - Ayuningtyas, Fitria; Irawatie, Aniek; Kurnia, Oktahara Tri (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
Marketing is an activity that is very important for a company to achieve its goals. Now that many competitors have similar products, companies must be able to determine the right strategy so that the company can continue to develop along with time. This study aims to determine how much are the impact of Samyang halal certificate products brand image on consumer attitudes. The concepts or theories that are relevant in this study include Stimulus-Organism-Response, Brand Image, and Consumer Attitudes. This research was conducted using a quantitative research approach. The research method used was a survey. The population of this research is ARMY ELS Medan, North Sumatra with 114 respondents. The sampling technique in this study used a saturated sampling method. The results of this study indicate that the correlation of variable X with variable Y is 0.754, this value means that it has a strong relationship because it is located between 0.600 - 0.799. Based on the calculation of the coefficient of determination, it is found that the effect of variable X on variable Y is 56.8%. Thus, it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a significant influence between the brand images of the Samyang halal certificate on consumer attitudes.